The short-term relationships among the U.S., German and Greek bond markets in times of financial crises. A Bayesian analysis of exogeneity in the VAR-SV model - Modrzejewska, Anita; Pajor, Anna (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
This paper examines short-run relationships among the U.S., German and Greek bond markets in times of financial crises. Specifically, the connections among daily and weekly growth rates of the 10-year government bond yields of the U.S., Germany and Greece from July 13, 2006 to January 29, 2016 are considered and an empirical illustration of those, based on the vector autoregressive (VAR) model with stochastic volatility (SV) disturbances, is provided. Finally, sufficient weak and strong exogeneity conditions in the VAR-SV models are tested. Our results indicate that during the time period covered by the analysis, the weekly growth rates of the 10-year U.S. bond yields were not affected by the past growth rates of the 10-year German and Greek bond yields. Contagion effects were absent among all the 10-year bond markets considered. From October 2008 to April 2015 a ‘flight to quality’ effect be-tween Germany and Greece, as well as between the U.S. and Greece seems to have occurred. Since the strong exogeneity hypothesis of the 10-year US bond yields’ weekly growth rates has not been rejected by the data, they can be predicted from the marginal model only, i.e. without taking the German and Greek bond yields into consideration
Argumenta Oeconomica, 2017, Nr 1 (38), s. 257-283
Keywords: international bond markets; financial crisis; exogeneity; stochastic volatility